2017
DOI: 10.1016/j.athoracsur.2016.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Failed Pulmonary Autografts Compared to Native Aortic Roots

Abstract: Failed pulmonary autografts retained a nonlinear response to mechanical loading typical of healthy arterial tissue. Despite similar wall thickness between autografts and aorta, autograft stiffness in this patient population was significantly reduced compared with native aortic roots. We demonstrated that biomechanical remodeling was inadequate in these specimens to achieve native aortic mechanical properties, which may have resulted in progressive autograft root dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…One report from Horer et al stated that there is not homogeneous dilatation of annulus, Valsalva sinus, and sinotubular junction, and an external barrier to protect these zones could be beneficial to avoid expansion of the pulmonary conduit [ 14 ]. Mookhoek et al [ 42 , 43 ] confirmed the nonlinear response to mechanical load typical of the biomechanical characteristics of healthy human arterial tissue in failed pulmonary autografts but warned about increased compliance and reduced wall stiffness of the PA in comparison to native pulmonary artery, providing an explanation for PA dilation [ 43 ]. In another study by the same group comparing failed PA root to native aorta, these authors confirmed the increased compliance of explanted PA roots in comparison to the aorta, but, notwithstanding the similar wall thickness, demonstrated the biomechanical remodeling inadequacy of the PA, which was characterized by a significant decrease in wall stiffness in comparison to native aorta [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One report from Horer et al stated that there is not homogeneous dilatation of annulus, Valsalva sinus, and sinotubular junction, and an external barrier to protect these zones could be beneficial to avoid expansion of the pulmonary conduit [ 14 ]. Mookhoek et al [ 42 , 43 ] confirmed the nonlinear response to mechanical load typical of the biomechanical characteristics of healthy human arterial tissue in failed pulmonary autografts but warned about increased compliance and reduced wall stiffness of the PA in comparison to native pulmonary artery, providing an explanation for PA dilation [ 43 ]. In another study by the same group comparing failed PA root to native aorta, these authors confirmed the increased compliance of explanted PA roots in comparison to the aorta, but, notwithstanding the similar wall thickness, demonstrated the biomechanical remodeling inadequacy of the PA, which was characterized by a significant decrease in wall stiffness in comparison to native aorta [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the FE analyses showed that the realistic response of the aorta-autograft ensemble cannot be captured by means of modeling simplifications, such as numerical simulations performed by taking into account the two vessels as separate entities [ 42 , 43 , 44 ]. The FE outcomes demonstrate that the interplay among material properties of the autograft and aorta, suture regions, geometry, and dilation constraints imposed by the annulus is crucial for determining the effects that actual stress concentrations, strain localization onsets, and deformation gradients have on the success of the Ross operation [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…and failed pulmonary autografts after the Ross procedure are characterized by increased collagen content 2,8,15 . The latter studies also reported variable intimal thickening, as was reported in pulmonary blood vessels of pulmonary hypertensive patients 16,17 .…”
Section: Effect Of Systemic Conditions On Autograft Dilatationmentioning
confidence: 99%
“…Many efforts are undertaken to model the adaptation processes that take place after exposing pulmonary artery to a new mechanical environment 14 . Studies examining the remodeling of failed pulmonary autografts, as well as studies investigating arterial remodeling following hypertension, mention an increased extracellular matrix deposition and, consequently, a change in mechanical properties 2,8,[15][16][17][18][19][20][21] . To our knowledge, quantitative experimental data on both the mechanical and histological adaptation of arterial tissue to external mechanical stimuli in a large animal model are currently non-existent.…”
mentioning
confidence: 99%
“…Our results show that a valveless pulmonary autograft placed in aortic position will remodel such that its macroscopic behavior leans more towards aorta-like behavior, as measured through planar biaxial tensile tests. In contrast, when studying excessively dilated pulmonary autografts in ten patients, Mookhoek et al [11,12] observed a decreased stiffness compared to both the native aorta and pulmonary artery, suggesting a failure of the tissue to remodel. Developing a mathematical model about this phenomenon may help to understand neoaortic valve failures, assuming that pulmonary (neoaortic) root dilatation is a major determinant of neoaortic valve regurgitation.…”
Section: Introductionmentioning
confidence: 94%